Recycling process of spent bleaching clay: Optimization by response surface methodology - A.M. Hatami; M.R. Sabour; A. Amiri (Global Journal of Environmental Science and Management)
Oil refining is an inevitable step in production of edible and industrial oil. Bleaching is the most important process among the refining processes. Bleaching adsorption is the most common method and clay is the most widely used adsorbent in this method. Disposal of bleaching clay, as a waste from re-refining plants, makes many environmental problems and economic losses. In the current study, the effects of possible factors such as solvent to clay ratio, temperature, time, aggregation size and rotation speed of the stirrer (degree of mixing) on the efficiency of extracted lubricating oil were investigated by solvent extraction method. By conducting experiments at different reaction times and rotation speeds, it was concluded that the most important factor in obtaining the appropriate output was solvent to clay ratio. The tests conducted to investigate the effect of grain size on the efficiency indicated that agglomerates size did not have a positive effect on efficiency. Finally, for the solvent to clay ratios ranging from 2.48-9.53 ml/g and a time period ranging from 5 to 40 minutes, the main tests designed by the response surface methodology. The best efficiency was obtained at the highest level of solvent to clay ratio (9.53 ml/g) and at the time of 22.5 minutes that led to 88.60% oil extraction from the clay. The accuracy of the model output was estimated to be 96%.